Innovation efficiency of high-tech industries in China - Ding, Ruosha (2016)
A measurement of technical innovation efficiency reflects the competitiveness of the high-tech industry for a region or a country. The high-tech industry, which appears at the forefront of technology and scientific research, provides a country with a certain competitive advantage. Many developed countries such as the USA, UK, Germany and France, have used the high-tech industry as a means to emerge on the technological frontier. Many developing countries such as China and India have developed high-tech industries, and are home to many leading product manufacturers. However, innovation efficiency is important, since it explains the efficiency of the high-tech industry in consuming resources and providing outputs. This dissertation examines the innovation efficiency of the high-tech industry in China. The Data Envelopment Analysis (DEA) method was used to study and analyse panel data. The study focused on 28 high-tech provinces of China (DMUs, DMU: Decision Making Unit), during the years 2005-2011, along with 5 industry categories and 17 industries. Different datasets were obtained to measure the input and output indices. Variables included in the inputs index included the number of full time R&D (Research and Development) personnel, internal expenditure on R&D, expenditure on new product development, and investment in fixed assets. The output index included the number of patent applications, the output value of new products, and sales revenue for new products.